Phenomenal contrast arguments for cognitive phenomenology - Chudnoff, Elijah; Cardona Muñoz, Elizabeth; Álvarez Céspedes, Juan Fernando (Estudios de Filosofía, 2018)
According to proponents of irreducible cognitive phenomenology some cognitive states put one in phenomenal states for which no wholly sensory states suffice. One of the main approaches to defending the view that there is irreducible cognitive phenomenology is to give a phenomenal contrast argument. In this paper I distinguish three kinds of phenomenal contrast argument: what I call pure—represented by Strawson’s Jack/Jacques argument —hypothetical— represented by Kriegel’s Zoe argument —and glossed— first developed here. I argue that pure and hypothetical phenomenal contrast arguments face significant difficulties, but that there is a sound glossed phenomenal contrast argument for irreducible cognitive phenomenology.